PENGGUNAAN ALAT PERAGA PENGUKURAN SUHU BERBASIS DIGITAL TERHADAP KETERAMPILAN PROSES SAINS - Anggereni, Santih; Said L, Muh; Nur, Hasan; Irwan, Anas (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2021)
this is a pre-experiment research which aims: 1) to know to what extent the students’ skill of science process in learning to measure the temperature by using digital based thermometer to the first semester students of Physics Education of Tarbiyah and Teaching Science Faculty at UIN Alauddin Makassar,? 2) to know how to use effective digital based thermometer toward the skill of science process to the first semester students of Physics Education of Tarbiyah and Teaching Science Faculty at UIN Alauddin Makassar? The research design used here is one shot case study. The population consists of 77 first semester students of Physics Education in UIN Alauddin Makassar. This population is divided into two classes. Meanwhile, It takes the sample type of simple radom sampling with the total of 30 people. The result of this study showed that the average score of students’ skill in science process after using digital based thermometer was 83,17. This score was in the level of category of high and very high. The result was also strengthened by the result of hypothesis test which utilized t-test. It was found that the tcalculate was 6,748 and the score of ttable was 1,697. Since the score of tcalculate was bigger than the ttable (tcalculate > ttable), thus the H0 was accepted and the Ha was rejected. Then, It could be concluded that the use of digital based thermometer was effective toward the skill of science process of the first semester students of Physics Education of Tarbiyah and Teaching Science Faculty in UIN Alauddin Makassar. The implication of this research can train students skill in learning science that are obtained in class. So they can develop students science process skill in the laboratory. The shortcomings of this research connot be maximized because of the lack of learning time, the next researcher is expected use more time to apply teaching aids to material that has many concepts